2019
DOI: 10.3390/w11050952
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Sediment Yield and Maximum Outflow Using the IntErO Model in the Sarada River Basin of Nepal

Abstract: Soil erosion is a severe environmental problem worldwide as it washes away the fertile topsoil and reduces agricultural production. Nepal, being a hilly country, has significant erosion disputes as well. It is important to cognise the soil erosion processes occurring in a river basin to manage the erosion severity and plan for better soil conservation programs. This paper seeks to calculate the sediment yield and maximum outflow from the Sarada river basin located in the western hills of Nepal using the comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 47 publications
1
62
0
1
Order By: Relevance
“…This increases the vulnerability of GAS in the region where a large part of the local population is concentrated. The piezometric surface reveals drawdown induced by the large concentration of wells and high pumping rates, mainly in the central region of the city (Montenegro et al, 1988;São Paulo, 2008;Conceição et al, 2009). In addition, in the outcrop region of the SAG, the level of groundwater has the lowest depths ( Figure 7A), which coincides with the lowest altitudes.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…This increases the vulnerability of GAS in the region where a large part of the local population is concentrated. The piezometric surface reveals drawdown induced by the large concentration of wells and high pumping rates, mainly in the central region of the city (Montenegro et al, 1988;São Paulo, 2008;Conceição et al, 2009). In addition, in the outcrop region of the SAG, the level of groundwater has the lowest depths ( Figure 7A), which coincides with the lowest altitudes.…”
Section: Resultsmentioning
confidence: 95%
“…With reference to expanding the use of the lowering cone (Conceição et al, 2009) it is suggested the tubular wells be constructed far away from the areas of highest exploitation, using alternate pumping methodologies to enhance the supply; another way is to regularize the water collection in the Rio Pardo subbasin, and set up environmental preservation areas and a vulnerability to pollution zone; one more method would be to improve agricultural management and control the types of fertilizers and pesticides applied and establish maximum permitted limits, in synchrony with intensive environmental education. Therefore, the hydrosedimentological dynamics in the specific area requires assessment to discover the water erosion hot spots, as revealed by the regions that exceed the established TPS limit ( Figure 8B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the obvious consequences are soil loss and changes in the land surface morphology; yet, the implications go much deeper. It is well documented that soil erosion leads to decline of soil fertility and to considerable loss of productive cultivated and arable land or even to desertification, with serious socioeconomic effects [3][4][5][6][7][8]. A degradation of physical properties of soil involves a decline in soil structure resulting to an increase in bulk density, decrease in total macroporosity, reduction in infiltration, and increase in surface runoff and, finally, in aggravation of soil erosion by water [9].…”
Section: Definition Of the Problemmentioning
confidence: 99%
“…For the appropriate sustainable watershed management, land use and landscape planning, which will more effectively meet national or local needs and assists in assessing the consequences of the alternatives the important issue is to quantify the sediments and to estimate sediment yield at the river basin scale (Chalise et al, 2019;Spalevic, 2019;Curovic et al, 2019;Parsipour et al, 2019, Fikfak et al, 2017Popovic et al, 2018). Sediment sampling in the rivers need a lot of time and costly laboratorial works.…”
Section: Introductionmentioning
confidence: 99%